PROSES PEMBENTUKAN KATA AFIKSASI PADA TUTURAN GURU DALAM PEMBELAJARAN MENULIS TEKS NEGOSIASI DI KELAS X SMA MUHAMMADIYAH 2 JOMBANG - Fitri Resti Wahyuniarti (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
The use of words that are not appropriate will lead to misinterpretation in interpreting a speech. In line with this opinion, this obstacle arises because students have not been able to put ideas into writing according to the correct diction, especially words formed by affixes, so the teacher must provide examples through speech during learning. The purpose of this study is to describe the process of forming prefix, suffix, infix, and simulfix affixes in learning to write negotiating texts in class X SMA Muhammadiyah 2 Jombang. This research is a type of qualitative descriptive research with stages: Observation, Research objectives, Data collection, Data analysis, Drawing conclusions, Compiling articles, Submitting articles to the national journal sinta 3 https://jurnal.unublitar.ac.id/index.php/ brilliant/index, and Reporting. This research was conducted in class X SMA Muhammadiyah 2 Jombang. Data collection was carried out in 3 ways, namely: documentation, observation, and interviews. Data analysis used interactive data analysis of the Milles Hubarmen model which included: data collection, data reduction (Identification, Classification, Description), data presentation (Coding, Table Making, Selection of affixation examples), and drawing conclusions (verification) by utilizing triangulation as a technique checking the validity of research findings. The results of this study are the formation of affixes by adding prefixes, suffixes, confixes, and simulfixes. The process of forming affixation by adding prefixes (ber-, di-), The process of forming affixation by adding suffixes (-i), forming affixes by adding confixes and simulfixes (MeN-kan).